(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2024)
Consensus is the engine that makes a blockchain trustworthy, but it is also the component that breaks first when a network grows. Classical BFT protocols like PBFT achieve strong safety guarantees yet collapse above a few dozen validators because their O(n squared) message complexity turns every new node into a burden on every existing one. Nakamoto-style proof-of-work scales to thousands of miners but sacrifices finality and wastes energy on an industrial scale. The newer generation of consensus mechanisms – HotStuff, Tendermint, Avalanche, DAG-based protocols, and hybrid constructions – promises to break this trade-off, but the claims are rarely tested under identical conditions at genuine enterprise scale. We present the Fault-Tolerant Consensus Benchmarking Framework (FTCBF), a head-to-head evaluation of seven consensus mechanisms across network sizes ranging from 4 to 500 validators, measuring throughput, finality latency, fault tolerance under active Byzantine attack, and recovery behaviour after partitions. We introduce the Consensus Quality Index (CQI) that balances throughput, latency, Byzantine resilience, scalability decay, and energy efficiency. Our results show that DAG-based consensus achieves the highest CQI at 0.912 for networks above 100 validators, while HotStuff variants dominate below that threshold. We also identify, and quantify for the first time, the "consensus cliff" – the validator count at which each mechanism’s throughput drops below 50% of its peak.